Teoria da (in)decisão política: uma investigação da democracia sitiada pela sondocracia - Henrique Jose da Silva Souza (2015)
This study aims to develop a line of reflection that would lead us since the dawn of democracy to its present condition, trying to grasp the thought of different political philosophers with the desire to also question the role of the citizen in this context. We will address the challenges faced by democracy on a society that, shipwrecked in a sea of knowledge, becomes so ignorant as to be completely manipulated. Therefore, the issue of Public Opinion, which shows how a critical moment of citizen participation against their government and their representatives and becomes central target of our analysis. Furthermore, we tried to demonstrate how the results expressed in opinions polls ultimately subject conditions the decisions of the representatives towards the demands appointed and hence interfere with the duty to decide the representative mandate.